Cultured fish cells metabolize octadecapentaenoic acid (all‐cis δ3,6,9,12,15–18∶5) to octadecatetraenoic acid (all‐cis δ6,9,12,15–18∶4) via its 2‐trans intermediate (trans δ2, all‐cis δ6,9,12,15–18∶5) - Ghioni, C.; Porter, A. E. A.; Sadler, I. H.; Tocher, D. R.; Sargent, J. R. (Lipids, 2001)
Abstract Octadecapentaenoic acid (all‐ cis δ3,6,9,12,15–18∶5; 18∶5n−3) is an unusual fatty acid found in marine dinophytes, haptophytes, and prasinophytes. It is not present at higher trophic levels in the marine food web, but its metabolism by animals ingesting algae is unknown. Here we studied the metabolism of 18∶5n−3 in cell lines derived from turbot ( Scophthalmus maximus ), gilthead sea bream ( Sparus aurata ), and Atlantic salmon ( Salmo salar ). Cells were incubated in the presence of approximately 1 μM [U‐ 14 C] 18∶5n−3 methyl ester or [U‐ 14 C]18∶4n−3 (octadecatetraenoic acid; all‐ cis δ6,9,12,15–18∶4) methyl ester, both derived from the alga Isochrysis galbana grown in H 14 CO 3 − , and also with 25 μM unlabeled 18∶5n−3 or 18∶4n−3. Cells were also incubated with 25 μM trans δ2, all‐ cis δ6,9,12,15–18∶5 (2‐ trans 18∶5n−3) produced by alkaline isomerization of 18∶5n−3 chemically synthesized from docosahexaenoic acid (all‐ cis δ4,7,10,13,16,19–22∶6). Radioisotope and mass analyses of total fatty acids extracted from cells incubated with 18∶5n−3 were consistent with this fatty acid being rapidly metabolized to 18∶4n−3 which was then elongated and further desaturated to eicosatetraenoic acid (all‐ cis δ8,11,14,17,19–20∶4) and eicosapentaenoic acid (all‐ cis δ5,8,11,14,17–20∶5). Similar mass increases of 18∶4n−3 and its elongation and further desaturation products occurred in cells incubated with 18∶5n−3 or 2‐ trans 18∶5n−3. We conclude that 18∶5n−3 is readily converted biochemically to 18∶4n−3 via a 2‐ trans 18∶5n−3 intermediate generated by a Δ 3 , Δ 2 ‐enoyl‐CoA‐iso‐merase acting on 18∶5n−3. Thus, 2‐ trans 18∶5n−3 is implicated as a common intermediate in the β‐oxidation of both 18∶5n−3 and 18∶4n−3.